Expression and distribution of activin-follistatin-inhibin axis in the urinary bladder - Mao, Weipu; Zhang, Tracy; Chen, Huan; Barge, Sagar; Wang, Zongwei; Olumi, Aria; Alper, Seth; Yu, Weiqun (Frontiers in Molecular Biosciences, 2025)
The activin-follistatin-inhibin (AFI) axis plays a crucial role in sexual development and reproduction. Recently it was demonstrated that these proteins are also synthesized by many local tissues and regulate different biological activities, including tissue regeneration and cancer metastasis. However, little is known about the expression profile of the AFI axis in the bladder and its role in bladder function and dysfunction. We have examined the expression profile of 11 AFI family members in the mouse bladder. INHA, INHBA, and follistatin are the major ligand subunits detected among the six examined in the bladder. ACVR1, ACVR1B, and ACVR2B are the major receptor subunits detected among the five examined in the bladder. Immunolocalization studies reveal unique cellular distributions of these ligands and receptors within the bladder. The urothelial-localized ACVR2B/ACVR1B receptor complex suggests a role of activin signaling in urothelial function. The stimulatory activin A is present only in a subset of interstitial cells, separated from the urothelial activin receptor ACVR2B/ACVR1B by a basement membrane containing accumulated inhibitory ligand FST and by a layer of activin-negative myofibroblasts. This spatial information on AFI signal molecules suggests that activin A-positive interstitial cells might regulate urothelial cell function via paracrine signaling through activin A-ACVR2B/ACVR1B interaction. Further analysis of the human bladder confirmed the expression profile of the AFI axis, and revealed significantly upregulated expression of INHBA–ACVR2B in bladder cancer. These data suggest roles for these molecules in the growth and metastasis of bladder cancer, and highlight their potential as diagnostic and prognostic biomarkers.